G2C acceptance in Malaysia: trust, perceived risk and political efficacy - Hussein, Ramlah; Mohamed, Norshidah; Ahlan, Abdul Rahman; Mahmud, Murni; Aditiarawan, Umar (2009)
Electronic government or e-government has long been known as a breakthrough of a new form of communication and transaction between the government and citizens, the government and industries, and among the government agencies. Simply, e-government is meant not only to help the government to accomplish its daily administrative activities but also to provide an easier way to communicate with external entities such as citizens and business throughout the utilization of information and communication technology (ICT). With the implementation of e-government in Malaysia, study about Government to citizens (G2C) adoption could be significantly important in reflecting its progress. Against this backdrop, this research intends to study G2C adoption in Malaysia by adopting Technology Acceptance Model (TAM) theory as a framework. We investigated factors that are believed to influence citizens' intention to use G2C system. The factors were trust, perceived risk and political efficacy.